2000
DOI: 10.1007/s100670050003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melatonin in Patients with Fibromyalgia: A Pilot Study

Abstract: The aim of the study was to determine the possible effect of melatonin treatment on disturbed sleep, fatigue and pain symptoms observed in fibromyalgia (FM) patients. Twenty-one consecutive patients with FM were included in an open 4-week-duration pilot study. Before and after treatment with melatonin 3 mg at bedtime, patients were evaluated using tender point count by palpation of 18 classic anatomical regions, pain score in four predesignated areas, pain severity on a 10 cm visual analogue scale (VAS), sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 18 publications
8
86
0
7
Order By: Relevance
“…On the other hand, the use of melatonin as single treatment for FMS patients significantly improves the total FIQ scores. This result was found comparable to that reported by Citera et al (2000) who demonstrate that treatment with 3 mg melatonin at bed time produced significant improvement in the pain score, measured by Visual Analog Scale (VAS), and sleep parameters were the mostly affected parameters compared to other variable, but without reaching significant level [26]. Moreover, the results of another clinical trial indicated that using 6 mg/day melatonin at night for 30 days, all the included FMS patients developed a relatively normal sleep/wake cycle, which accompanied by significant reduction in pain and improvement of behavioral symptoms [27].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the use of melatonin as single treatment for FMS patients significantly improves the total FIQ scores. This result was found comparable to that reported by Citera et al (2000) who demonstrate that treatment with 3 mg melatonin at bed time produced significant improvement in the pain score, measured by Visual Analog Scale (VAS), and sleep parameters were the mostly affected parameters compared to other variable, but without reaching significant level [26]. Moreover, the results of another clinical trial indicated that using 6 mg/day melatonin at night for 30 days, all the included FMS patients developed a relatively normal sleep/wake cycle, which accompanied by significant reduction in pain and improvement of behavioral symptoms [27].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that melatonin produces a transient antinociceptive effect in rats and mice (Yu et al, 2000a, b;Tu et al, 2004;Onal et al, 2004), modulates lipopolysaccharideinduced hyperalgesia possibly via its influence on the role of proinflammatory cytokines in sensory neurons , and interacts with opioid antinociception (Golombek et al, 1991;Pang et al, 2001;Li et al, 2005;Shavali et al, 2005). In clinical studies, melatonin has been reported to reduce cluster headache, irritable bowel syndrome, and fibromyalgia (Leone et al, 1996;Citera et al, 2000;Song et al, 2005), although the relationship between depression and chronic pain was not specifically examined in these clinical reports. Evidence also exists that implicates melatonin for the mood regulation (Brzezinski, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Так, были получены клинические данные об эффективности мела-тонина при кластерных головных болях и мигрени. Име-ются данные об его эффективности при фибромиалгии, полученные в ходе открытого рандомизированного иссле-дования [3]. Мелатонин назначался по 3 мг за 30 мин до сна в течение 4 нед.…”
Section: Discussionunclassified